Implementation of “Kaizen–process innovation–jidoka” techniques to deal with Covid-19: a case study in a public hospital - Suárez-Barraza, Manuel F. (2020)
Mexico’s public hospitals are experiencing major operational problems, such as process and service failure, as well as the lack of supplies and medical equipment. Some hospitals have started kaizen philosophy-based efforts to improve this situation. The main objective of the research is to explore the implementation of the kaizen philosophy in the above-mentioned hospitals. The research used a qualitative methodology and the case study strategy. The results show that it is feasible to optimize the Covid-19 emergency and treatment process by applying kaizen philosophy, process innovation and jidoka techniques.